Fibonacci and Lucas identities through colored tilings - Benjamin, Arthur T.; Quinn, Jennifer J. (Utilitas Mathematica, 1999)
In this paper we introduce the concept of colored Fibonacci tilings which leads to charming combinatorial proofs of Fibonacci and Lucas number identites.